THERAPEUTIC VALUE OF ARCTIUM LAPPA LINN. – A REVIEW - GOWHER GUNA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Arctium lappa (AL) (Burdock) has been used for centuries to treat a variety of ailments. Extracts of burdock root (BR) are found in a variety of herbal preparations, as well as homeopathic remedies. Arctium has been used as medicine and health supplement for hundreds of years in Europe, North America, and Asia. It is popular as a medicinal plant in traditional Chinese medicine where it is extensively used for various ailments. In recent years, immense phytochemical and pharmacological screening of Arctium has shown tremendous activity against various diseases. The plant has shown biological activity as anti-inflammatory, antiallergic, antidiabetic, antineoplastic, antimutagenic, antiviral, urolytic, antitoxic, antileukemic, hepatoprotective, growth stimulating, mild laxative, mild diuretic, depurative, diaphoretic, antibacterial, antirheumatic, and antipyretic agent. The present review highlights botanical description, distribution, chemical constituents, and the pharmacological effects of AL. The aim of this review is to correlate active principles of the plant to their pharmacological activity and thus explore the potential of AL as a source of therapeutic agents.